Increasing the Economy Through MSME Marketing via Social Media - Mukhlisin; Indriani, Dian Eka; Iristian, Jovi; Prayudanti, Adhania Andika; Shah, Abrisam (STAI Miftahul ULa Nganjuk, 2025)
The assistance provided to MSMEs in Sambiroto Village aims to enhance the competitiveness and capacity of MSME actors through the utilization of social media as a tool for digital marketing. The focus of this community service is to address the limitations of conventional marketing, which is confined to the local market, by leveraging digital platforms such as Instagram, Facebook, and YouTube. The methods employed include training on creating social media accounts, content management, and strategies for interacting with consumers to expand market reach. The results of the service show that after the assistance, MSMEs were able to improve the visibility of their products, broaden their market reach, and experience an increase in sales. This program also helped MSME actors better understand the importance of digital marketing and integrate it into their business strategies, significantly strengthening their competitiveness in the digital era.